Successful treatment with fludarabine and cyclophosphamide in a VEXAS syndrome patient with associated myelodysplastic syndrome: a case report and systematic review - Bellman, Polina; Gonzalez-Lugo, Jesus D.; Shahzad, Moazzam; Amin, Muhammad Kashif; Khalid, Muhammad Fareed; Suleman, Nahid; Ahmed, Nausheen; Singh, Anurag K.; Yacoub, Abdulraheem; Zhang, Da; McGuirk, Joseph P.; Mushtaq, Muhammad Umair (Frontiers in Oncology, 2024)
Vacuoles, E1 syndrome, X-linked, autoinflammatory, somatic (VEXAS) syndrome is a chronic inflammatory disorder that affects various organ systems. It is associated with hematologic malignancies and is generally refractory to therapies. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) may be considered for selected patients. We report a case wherein systemic and hematological manifestations completely resolved in a patient with VEXAS and associated myelodysplastic syndrome (MDS), following the administration of fludarabine and cyclophosphamide as part of the preparation for allo-HSCT. We conducted a systematic literature review and included 86 patients with VEXAS syndrome and associated MDS. Most cases presented with musculoskeletal involvement (71%) and anemia (72%) with lower-risk MDS. Most patients responded to corticosteroids (CS) but had a recurrence of symptoms with CS taper and were refractory to other immunosuppressive agents. Hypomethylating agents and Janus kinase inhibitors achieved a complete response in some cases. Further research is needed to develop more effective treatment strategies.